Examining the Influence of Relational Aggression on Sexual Satisfaction With Attachment Behaviors as a Potential Mediator. Issue 5 (4th July 2018) - Sandberg, Jonathan; Meservy, Melece Vida; Bradford, Angela; Anderson, Shayne
ABSTRACT: The purpose of this study was to investigate the relationship between relational aggression and sexual satisfaction, as well as to determine if attachment behaviors could mediate this relationship. Data came from the Relate Institute Questionnaire (RELATE) and were drawn from the matched-pair responses of 539 heterosexual married couples. Results showed the greater the perceived relational aggression, the lower the sexual satisfaction for both self and partner, regardless of gender. Mediation analyses suggest that attachment behaviors may be a mechanism through which relational aggression influences sexual satisfaction. Implications for clinicians and future research are discussed.